Factors Associated with Parental and Adult Personal Underestimation of Overweight Status - Alshahrani, Abrar (2023)
Parents of children with overweight or obesity often fail to identify their child's weight status. Similarly, adults with overweight or obesity often inaccurately identify their own overweight status. The factors associated with parental and adult personal underestimation of overweight and obesity are still unclear, and they represent the primary focus of this thesis. Study 1 systematically reviews published research to investigate the prevalence of, and factors associated with, the underestimation of children’s weight status in parents, healthcare professionals and children themselves. Quantitative and qualitative data were critically reviewed to increase comprehension by exploring any linked factors. It was determined that underestimation of children’s overweight is common across a range of nations. With the use of a verbal scale, 55% parents underestimated excess weight and obesity in their children. Use of a visual scale gave rise to a slightly lower, 47% prevalence of underestimation. Children and adolescents also underestimated their own weight status with a prevalence estimate of 34%. HCPs share the same misperception however limited data prevent meta-analysis. Overall, underestimation was positively associated with children’s age, gender, child and parent’s current weight status, parental educational level and ethnicity. In the qualitative studies, parents commonly describe their children in different terms other than ‘obese’. Terms such as “big boned”, “thick” and “solid” were used, and demonstrated a strong desire to avoid labelling their child by using medical terminology. Study 2 examines adult personal underestimation of overweight status and the factors associated with this underestimation using quantitative methodology. Among 1061 participants, 43% of participants with overweight and 66% of the participants with obesity underestimated their weight status using a verbal scale, while 29% of participants with overweight and 12% of the participants with obesity underestimated their weight status using a visual scale. Underestimation was associated with gender, age (older participants), current BMI, and lower educational level. This study contributes to the existing literature on social norms and other psychological factors and suggests that individuals who have high levels of fear of obesity (negative emotions associated with obesity diagnosis) were more likely to underestimate their weight status. In addition, underestimation of overweight and obesity was most common among individuals frequently exposed to obesity in their everyday lives. The findings of study 2 found that participants who selected an overweight silhouette as an average body shape were more likely to underestimate their weight status. In this study, there was a greater accuracy when the visual scale was used compared to a verbal scale. Finally, Study 3 builds on the findings of study 1 and 2 and aims to provide a comprehensive empirical investigation of the relationship between sociodemographic, anthropometric, and psychological factors in adults’ underestimation of the overweight and obese status of children. In this questionnaire-based study underestimation of overweight status was associated with child’s age, gender, current BMI, parents and grandparents’ gender. Further, parents and grandparents who had a high level of negative emotions associated with a child being diagnosed as obese, were more likely to underestimate their child’s weight. Finally, high levels of internalised weight bias were associated with higher rates of parental underestimation of child weight. The overall findings of this thesis clearly show that parental and adult personal underestimation of overweight status is widespread. Such under-estimations may significantly delay appropriate interventions to prevent the negative health associated impacts of excessive weight and the thesis identifies urgent need for further research to explore how to overcome the existing barriers towards a more realistic recognition of weight status.